2014
DOI: 10.1371/journal.pone.0085754
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Evolutionary Characterization of the CONSTANS Gene Family in Short-Day Photoperiodic Flowering in Soybean

Abstract: CONSTANS (CO) plays a central role in photoperiodic flowering control of plants. However, much remains unknown about the function of the CO gene family in soybean and the molecular mechanisms underlying short-day photoperiodic flowering of soybean. We identified 26 CO homologs (GmCOLs) in the soybean genome, many of them previously unreported. Phylogenic analysis classified GmCOLs into three clades conserved among flowering plants. Two homeologous pairs in Clade I, GmCOL1a/GmCOL1b and GmCOL2a/GmCOL2b, showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
103
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 59 publications
1
103
0
1
Order By: Relevance
“…Several studies in both monocots (Miller et al 2008;Nemoto et al 2003;Hayama and Coupland 2004) and dicots (Chia Putterill et al 1995;Suarez-Lopez et al 2001;Wong et al 2014;Zhang et al 2015;Wu et al 2014) have shown that photoperiod responsive flowering is controlled by the CO/FT module. The control is exerted by a combination of the circadian regulation of the CO gene and differential stability of the transcript and protein in light and dark.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies in both monocots (Miller et al 2008;Nemoto et al 2003;Hayama and Coupland 2004) and dicots (Chia Putterill et al 1995;Suarez-Lopez et al 2001;Wong et al 2014;Zhang et al 2015;Wu et al 2014) have shown that photoperiod responsive flowering is controlled by the CO/FT module. The control is exerted by a combination of the circadian regulation of the CO gene and differential stability of the transcript and protein in light and dark.…”
Section: Discussionmentioning
confidence: 99%
“…Under long day conditions, the CO protein is degraded in the dark and in the early morning by PHYB (red-light receptor) while it is stabilized in the evening by PHYA (far-red receptor) and CRYPTOCHROME 1 (CRY1) and CRY2 (blue-light receptor). In the afternoon CO protein is stabilized through interaction with FKF1 because of the antagonistic effect of PHYA (Song et al 2013;Wu et al 2014). The final result of the regulated expression of CO in long day plants such as Arabidopsis is its abundance during afternoon and a peak in the evening of a long day season.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the variation in B-box domains, the COL gene family in A. thaliana may be separated into three groups (Robson et al, 2001). Wu et al (2014) identified 26 CO homologs (GmCOLs) in the soybean genome and classified them into three clades, which are conserved among flowering plants. Chou et al (2013) identified 12 full-length E. pusilla CO-like (EpCOL) genes and divided them into four groups.…”
Section: Introductionmentioning
confidence: 99%
“…Majer Yang et al, 2006Stahle et al 2009Lugassi et al, 2010;Bonaccorso et al, 2012Yamada et al, 2011Wang et al, 2009cVosnakis et al, 2012Toriba et al, 2007Dai et al, 2007 Xiang et al, MatĂ­as-HernĂĄndez et al, 2010;Kapazoglou et al, 2012Gramzow et al, 2014Kapazoglou et al, 2012Kapazoglou et al, 2012Ishikawa et al, 2011Kapazoglou et al, 2012 LeClere Fornara et al, 2009;Bu et al, 2014;Yang et al, 2014Griffiths et al, 2003Wu et al, 2014Griffiths et al, 2003Tsuji et al, 2011Yang et al, 2014Miller et al, 2008Takada and Goto, 2003Lv et al, 2014Pin et al, 2010Faure et al, 2007Nan et al, 2014Komiya et al, 2008Hecht et al, 2011Navarro et al, 2011Lv et al, 2014Ng and Yanofsky, 2001DorcaFornell et al, 2011;Liu et al, 2013Moyle et al, 2014Schmitz et al, 2000Wei et al, 2014Huang et al, 2014Schmitz et al, 2000<...>…”
mentioning
confidence: 99%